PENGARUH INTERNET DAN MOTIVASI TERHADAP HASIL PENYELESAIAN TUGAS PELAJARAN DASAR DESAIN GRAFIS - Syarifah Raspi Anita; Elfi Tasrif (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to find out how much benefit the influence of the internet and motivation on the results of the completion of class X assignments on the basic subjects of graphic design. As for the type of research used is associative correlational research between quantitative approaches. The population in this research is addressed to multimedia class X students as many as 30 students. Data collected using a questionnaire method that has been compiled with documentation. The data collection techniques in the study used slake likert, namely by giving questionnaires to students of class X Multimedia at SMK N 3 Aceh Barat Daya as respondents in this study. Questionnaires and instruments are arranged on the basis of indicators that have been determined in this research. Research results indicate: 1). There is a positive influence between the use of the internet on the results of the completion of assignments in the multimedia X class whose count value tcount> ttable (3,809> 1,697) contributes 34.1% 2). There is a positive and significant influence on learning motivation towards the results of task completion in the X class multimedia students whose tcount> ttable (3,918> 1,697) contributes 35.1% and 3). there was a simultaneous influence between the use of the internet and learning motivation on the results of the task completion of the f count value (13,824> 2,292) giving a contribution of 50.6%. Keywords: Internet Utilization, Learning Motivation, and Results of Completing assgnments